Exploring Prey Selectivity and Feeding Habits of Wels Catfish (Silurus glanis L., 1758) in a Deep Anatolian Reservoir: Seasonal, Length, and Age-Dependent Diet Analysis - Ramazan Yazici; Mahmut Yilmaz; Okan Yazicioğlu (Aquaculture Nutrition)
Feeding habits and dietary preferences of wels catfish (Silurus glanis) were investigated in Sıddıklı Dam Lake through the examination of 200 individuals. The results revealed that the species predominantly exhibited piscivorous feeding characteristics, with Tinca tinca (IRI% = 78.93) identified as the primary food source. The food items in the stomach showed a wide spectrum, ranging from benthic invertebrates, crustaceans, molluscs, amphibians, and mammals to fishes. The study not only assessed the general food composition of wels catfish but also delved into the seasonal variations in diet composition. It was found that the stomach fullness index (FI) varied significantly among the seasons, with Winter showing the highest values (0.827). On the other hand, the lowest value was detected in the Autumn season (0.480). Age and length groups were also considered, with notable differences in stomach FI and diet composition observed across different stages of growth. Food preference analysis highlighted the selective tendencies of wels catfish towards certain food types, with Atherina boyeri and T. tinca emerging as preferred choices in different size groups. For small, medium, and large length individuals, the most preferred prey fish were A. boyeri (Va = 0.39518, χ2 = 31.2336), T. tinca (Va = 0.63564, χ2 = 82.8073) and T. tinca (Va = 0.666495, χ2 = 88.4307), respectively. The findings provide valuable insights into the feeding behaviour of wels catfish, underscoring the importance of understanding these patterns for effective management and conservation efforts. Further research should aim to explore the ecological implications of these feeding habits on the overall aquatic ecosystem.